Media enhancement for biomass of effective microbes (E.M.) via automated media optimization system for biofertilizer formulation / Aimi Nadia Saharuddin - Saharuddin, Aimi Nadia (2022)
The development of the agriculture sector acts as a base for the overall development of other sectors of the economy. It is vital to strategize ways to increase the production of agricultural products and improve soil vitality. The biofertilizer application is deemed today to limit the use of inorganic fertilizer and supports an effective tool for developing a green environment. The Effective Microbes (E.M.) biomass stock is in high demand as an additive in biofertilizer formulation as they improve soil-crops vitality and productivity. Nonetheless, the bio-productivity of the E.M. biomass stocks is unsurpassed by the demand due to non-optimized media and the use of the one factor at a time (OFAT) method, which is a less effective method. Thus, adopting a strategic approach is needed to overcome the issue. This research aimed to develop an optimized economic E.M. media with high yield and cost-effectiveness. This research intended to identify three objectives that affect E.M. growth performance; i) key nutrients, ii)nutrient interactions and media formulation, and iii) E.M. reproducibility from microlitre scale to flask scale. The effective method of the study utilizes a high throughput Automated Media Optimization System (AMOS) and bioreactor based on a 96-microwell-plate). Three experimental phases aligned to the objectives are; phase 1 examined for vital nutrient screening, and phase 2 screened for the other micro and macronutrients (a total of 180 formulations) to formulate optimized media for E.M. biomass growth enhancement. The media optimization system utilized the Box-Behnken Design. To analyze the experimented data resulting from the screening, response-surface methodology (Main Effects and Interaction Effects) was applied to determine the formulations' key nutrients and nutrient interactions using Minitab 18 software. In Phase 3, the optimal media derived from the previous experiments were subjected to large-scale (1 L flask) reproducibility tests. In key nutrients screening, highest growth performance of EM was achieved in the supplemented media, for B. subtilis (0.07248 h-1, 6.0 g/L YE + 40.0 mM G), C. utilis,(0.0795 h-1, 12 mM (NH4)2SO4 + 42 mM G), P. acidilactici (0.18433 h-1, 10 g/L BE +0.125 mM Mn), R. palustris (0.14557 h-1, 7.2 mM YE + 40 mM SB), and B. borstelensis(0.102 h-1, 4.0 g/L YE + 10 mM SB). For the nutrient interaction screening, the highest growth rate was attained at hour 2, and the doubling time was calculated as the followings – B. subtilis (2.782 h-1, 0.42 h), C. utilis (2.3175 h-1, 0.44 h), P. acidilactici(0.3831 h-1, 0.62 h), R. palustris (1.2029 h-1, 0.56 h), and B. borstelensis (0.9272 h-1,0.62 h). The nutrients' Main and Interaction Effects analysis was subjected to the pvalue.The other effective microbes exhibited significant main effects except P.acidilactici and B. borstelensis. The pairwise nutrient interactions were also observed for all effective microbes. High biomass yields were obtained for the reproducibility test in the low rate media - 1.384 g/L for B. subtilis, 0.030 g/L for P. acidilactici, 0.388g/L for R. palustris, and 1.563 g/L for B. borstelensis, whereas for C. utilis yielded0.188 g/L in high rate medium. This research allows the understanding of nutrient interactions that control the induction of high growth performance and specific novel functions of various E.M. Also, novel and optimized media formulations were generated. The results obtained from this research, coupled with the effective utilization of AMOS, can greatly benefit the agriculture sector specifically, consumers and the community in general. In the future, more accomplishments can be achieved as compared to the current conventional practices.